Ang anak ni Brocka - Barros-Sanchez, Sigfried; Lino Brocka; Buencamino, Nonie; Santos, Roence; Plata, Bimbi; Ramirez, Adrian (Sampaguita Pictures, 2005)
A group of investigative journalist accidentally score a controversial scoop when they find a twenty year old boy claiming to be the son of the late famous director Lino Brocka. Featured in the film are the works, friends and co-filmmakers of the late national artist for film.